Resuscitation with epinephrine worsens cerebral capillary no-reflow after experimental pediatric cardiac arrest: An in vivo multiphoton microscopy evaluation. Issue 12 (December 2022) - Oghifobibi, Onome A; Toader, Andrew E; Nicholas, Melissa A; Nelson, Brittany P; Alindogan, Nicole G; Wolf, Michael S; Kline, Anthony E; Nouraie, Seyed M; Bondi, Corina O; Iordanova, Bistra; Clark, Robert SB; Bayır, Hülya; et al.
Epinephrine is the principal resuscitation therapy for pediatric cardiac arrest (CA). Clinical data suggest that although epinephrine increases the rate of resuscitation, it fails to improve neurological outcome, possibly secondary to reductions in microvascular flow. We characterized the effect of epinephrine vs. placebo administered at resuscitation from pediatric asphyxial CA on microvascular and macrovascular cortical perfusion assessed using in vivo multiphoton microscopy and laser speckle flowmetry, respectively, and on brain tissue oxygenation (PbO2 ), behavioral outcomes, and neuropathology in 16–18-day-old rats. Epinephrine-treated rats had a more rapid return of spontaneous circulation and brisk immediate cortical reperfusion during 1–3 min post-CA vs. placebo. However, at the microvascular level, epinephrine-treated rats had penetrating arteriole constriction and increases in both capillary stalling (no-reflow) and cortical capillary transit time 30–60 min post-CA vs. placebo. Placebo-treated rats had increased capillary diameters post-CA. The cortex was hypoxic post-CA in both groups. Epinephrine treatment worsened reference memory performance vs. shams. Hippocampal neuron counts did not differ between groups. Resuscitation with epinephrine enhanced immediate reperfusion but produced microvascular alterations during the first hour post-resuscitation, characterized by vasoconstriction, capillary stasis, prolonged cortical transit time, and absence of compensatory cortical vasodilation. Targeted therapies mitigating the deleterious microvascular effects of epinephrine are needed.